Aromaterapi Kenanga Dibanding Lavender terhadap Nyeri Post Sectio Caesaria - Wasis Pujiati; Meily Nirnasari; Hotmaria Julia Dolok Saribu; Daratullaila Daratullaila (Jurnal Keperawatan Silampari, 2019)
This study aims to compare the effect of cananga and lavender aromatherapy on pain intensity in postoperative patients with Sectio caesaria . This research method uses true experimental design, randomized pretest posttest design. Sampling technique with simple random sampling. intervention group I was given aromatherapy cananga and group II was given lavender aromatherapy. Changes in pain intensity are measured using a Numerical Rating Scale. The pain felt by patients before inhaling cananga aromatherapy is an average of 5.00 (moderate pain) and after therapy of 3.25 (mild pain). Pain that was felt by patients before inhaling lavender aromatherapy was an average of 4.83 (moderate pain) and after therapy of 3.25 (mild pain). The results of the analysis with the Wilcoxon test (p value 0,000) showed that there was an influence of cananga and lavender aromatherapy interventions using inhalation techniques to the intensity of pain in post sectio caesaria patients. Mann Whitney Test results obtained p value 0.054. Conclusions There is no significant difference in the effect of intervention from the two groups, meaning that both interventions have the same effective effect in reducing the intensity of pain in post-sectional cesarean patients. Keywords: Aromatherapy Canangium Odoratum, Lavandula, Pain, Sectio caesaria